Beda Pengaruh Post Isometric Relaxation dan Stretching Exercise terhadap Penurunan Nyeri Leher Non Spesifik : Studi Kasus - Ananta, Diella Khaerani; Haritsah, Nurul Fithriati; Ghufroni, Afif (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: Non-ergonomic work positions and monotonous postures, when maintained for extended periods, can have detrimental effects on workers, leading to muscle tension in the neck and shoulders, which may result in neck pain. Non specific neck pain refers to pain that can be provoked by static neck postures over long durations, neck movements, and tenderness upon palpation of cervical muscles without accompanying pathological conditions. Physiotherapy interventions that can be applied to reduce non-specific neck pain include post-isometric relaxation and stretching exercises. Objectives: To determine which intervention is more effective between post-isometric relaxation and stretching exercises in reducing non-specific neck pain. Methods: An experimental study with a two-group pre-and-post test design was conducted over two weeks in September 2024. Subjects were workers in a garment factory who met the inclusion criteria. A total of 52 subjects were randomly divided into two groups. Group I (n=27) received treatment through post isometric relaxation, while Group II (n=25) received treatment through stretching exercises. The Visual Analog Scale (VAS) was used to measure the reduction in neck pain. Results: Based on the results of the pre-post test statistical test of groups I and II, a value of p = 0.000 (p< 0.05) was obtained, which means that there is an effect of the pre-post test statistical test of groups I and II. For the post-test statistics of groups I and II, a value of p = 0.000 (p < 0.05) This indicates a difference in effect, with a mean difference of 26.51 in the PIR group and 14.2 in the stretching exercise group.Conclusion: Post-isometric relaxation is more effective in reducing pain in non-specific neck pain. Keywords: Non-specific neck pain, Post isometric relaxation, Stretching exercise, Visual Analogue Scale (VAS).